Digitally Financed Energy : How Off-Grid Solar Providers Leverage Digital Payments and Drive Financial Inclusion - Waldron, Daniel; Faz, Xavier (World Bank, Washington, DC, 2016)
The expansion of digital finance systems in the developing world has altered this financial context and enabled new business models that rely on small, regular payments. In the off-grid energy sector a group of solar companies, primarily in East Africa and South Asia, are leveraging digital finance to offer pay-as-you-go (PAYG) energy. This brief explains how digital finance is enabling PAYG energy expansion, which in turn provides a gateway to a range of financial products for the financially excluded.